Graft-repositioning technique using infusion and small bubbles during Descemet’s membrane endothelial keratoplasty - Toshiki Shimizu; Itaru Oyakawa; Daisuke Tomida; Hideaki Yokogawa; Akira Kobayashi; Satoru Yamagami; Takahiko Hayashi (BMC Ophthalmology)
Abstract Background Descemet’s membrane endothelial keratoplasty (DMEK) is a highly effective procedure for corneal endothelial dysfunction; however, once a DMEK graft is deployed, repositioning can be challenging. Therefore, this study aimed to evaluate the efficacy of a technique that utilizes infusion and small air bubbles to reposition a misaligned deployed graft. Methods This retrospective interventional case series enrolled patients who underwent DMEK between January 2022 and July 2023, including cases where the DMEK graft was attached and unfolded in off-center positions”. Experienced surgeons performed DMEK by inserting an infusion cannula and positioning a small bubble in the anterior chamber after the graft unfolded off-center. The eye was tilted in a deviated direction, and the cornea was massaged from the corneal limbus to the center using a 27-gauge blunt needle. Before and after DMEK, we measured the best spectacle-corrected visual acuity (BSCVA), central corneal thickness (CCT), and endothelial cell density (ECD). Additionally, we monitored the incidence of postoperative complications. Results Six eyes of six patients were included in this study. Postoperatively, the overall BSCVA and CCT of the eyes improved (P < 0.001). However, one eye developed recurrent uveitis and required a sub-Tenon’s capsule triamcinolone acetonide injection. No eyes required re-bubbling, and no instances of primary graft failure were observed. Conclusion The described technique enables the safe and feasible repositioning and unfolding of the DMEK graft.